Targeting Myeloid-Derived Suppressor Cells to Bypass Tumor-Induced Immunosuppression - Fleming, Viktor; Hu, Xiaoying; Weber, Rebekka; Nagibin, Vasyl; Groth, Christopher; Altevogt, Peter; Utikal, Jochen; Umansky, Viktor (Frontiers in Immunology, 2018)
The immune system has many sophisticated mechanisms to balance an extensive immune response. Distinct immunosuppressive cells could protect from excessive tissue damage and autoimmune disorders. Tumor cells take an advantage of those immunosuppressive mechanisms and establish a strongly immunosuppressive tumor microenvironment (TME), which inhibits anti-tumor immune responses, supporting the disease progression. Myeloid-derived suppressor cells (MDSC) play a crucial role in this immunosuppressive TME. Those cells represent a heterogeneous population of immature myeloid cells with a strong immunosuppressive potential. They inhibit an anti-tumor reactivity of T cells and NK cells. Furthermore, they promote angiogenesis, establish pre-metastatic niches and recruit other immunosuppressive cells such as regulatory T cells. Accumulating evidences demonstrated that the enrichment and activation of MDSC correlated with tumor progression, recurrence, and negative clinical outcome. In the last few years, various pre-clinical studies and clinical trials targeting MDSC showed promising results. In this review, we discuss different therapeutic approaches on MDSC targeting to overcome immunosuppressive TME and enhance the efficiency of current tumor immunotherapies.